Mixed-signal and DSP design techniques - Kester, Walt.; Analog Devices, inc. (Amsterdam ; Boston : Newnes, 2003)
The reader is provided with information on how to choose between the techniques and how to design a system that takes advantage of the best features of each of them. Imminently practical in approach, the book covers sampled data systems, choosing A-to-D and D-to-A converters for DSP applications, fast Fourier transforms, digital filters, selecting DSP hardware, interfacing to DSP chips, and hardware design techniques. It contains a number of application designs with thorough explanations. Heavily illustrated, the book contains all the design reference information that engineers need when developing mixed and digital signal processing systems. *Brought to you from the experts at Analog Devices, Inc. *A must for any electrical, electronics or mechanical engineer's reference shelf *Design-oriented, practical volume.
Introduction; Sampled Data Systems; Analog-to-digital Converters for DSP Applications; Digital-to-analog Converters for DSP Applications; Fast Fourier Transforms; Digital Filters; DSP Hardware; Interfacing to DSPs; DSP Applications; Hardware Design Techniques; Index.
Published in association with Analog Devices.
Includes bibliographical references and indexes.
Keywords: Signal processing; Signal processing -- Digital techniques; Mixed signal circuits -- Design; Electronic books